Case Report: Myelodysplastic/myeloproliferative neoplasm with concurrent SF3B1, ASXL1, JAK2 and CBL mutations and <15% bone marrow ringed sideroblasts - Wang, Yifan; Jin, Shengyu (Frontiers in Oncology, 2025)
This first-reported case of SF3B1-mutated myelodysplastic/myeloproliferative neoplasm with thrombocytosis (MDS/MPN-SF3B1-T), harboring coexisting ASXL1, JAK2 p.R683G, and CBL mutations challenges conventional genomic prognostic paradigms. A 72-year-old woman presented with anemia (Hb 91 g/L), thrombocytosis (Platelets 502×109/L), and 10% bone marrow ring sideroblasts, fulfilling 2022 WHO diagnostic criteria through molecular precedence of SF3B1 p.K700E (VAF 40.5%) despite subthreshold sideroblasts. Comprehensive genomic profiling revealed a unique quadruple mutation signature: ASXL1 p.G646Wfs*12 (9.8% VAF), JAK2 p.R683G (17.5%), and CBL p.R149Q (16.2%), with preserved karyotype. Functional analyses demonstrated mutation-specific pathobiological crosstalk: 1) SF3B1-mediated mitochondrial iron mislocalization (ALAS2 splicing defects, ABCB7 downregulation) synergized with ASXL1-driven epigenetic repression of erythroid transcription factors (GATA1, KLF1), exacerbating anemia; 2) JAK2 p.R683G’s partial kinase activation combined with CBL-dependent RAS/MAPK signaling sustained thrombocytosis through megakaryocytic hyperplasia. Despite harboring high-risk ASXL1 truncation, the patient maintained hematologic stability for six months without therapy, exhibiting declining platelet counts and improving Hb. This apparent genotype-phenotype discordance was attributed to clonal equilibrium (SF3B1 dominance suppressing ASXL1 leukemogenicity) and mutation-specific signaling attenuation (JAK2 R683G’s suboptimal kinase activation). Our findings necessitate revision of therapeutic algorithms for molecularly complex, treatment-naive elderly patients, particularly in resource-limited settings where socioeconomic factors critically influence management strategies.